Data Visualization of Poverty Level at Provinces in Indonesia from The year 2013-2015 - Stevencua Stevencua; Johan Setiawan (Universitas Multimedia Nusantara, 2018)
The aim of this paper is to create a data visualization that can convey information on poverty distribution of every province in Indonesia and to find a connection with education level. The method used is Eight-step data visualization and data mining methodology. Data for this research are taken from BPS from the year 2013 to 2015. Data collected after the data extracted and cleansing is 6000 records. Time needed to convert data from several publications and put it into one Excel file is 2 weeks. Tableau is chosen as tools for creating the Data Visualization. With this tools, data showed in a story dashboard which consists of 3 dashboards. The first dashboard is a mapping of poverty data onto provinces of Indonesia. The second dashboard is a mapping and distribution of education levels on cities and counties in Indonesia. The third dashboard is showing a ranking of areas with the highest percentage level of a citizen of education lower than elementary school in Indonesia. Based on the User Acceptance Test to BPS staff, authors have been able to produce the Story required, and interactive. As a conclusion from Data Visualization has been made, high poverty in certain areas not immediately is directly proportional to the level of education. Index Terms — Dashboard; data visualization, poverty, Tableau